2015
DOI: 10.1158/1940-6207.capr-14-0329
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Markers of Altered Nucleotide Metabolism in Early Stage Adenocarcinoma

Abstract: Adenocarcinoma, a type of non-small-cell lung cancer (NSCLC), is the most frequently diagnosed lung cancer and the leading cause of lung cancer mortality in the United States. It is well documented that biochemical changes occur early in the transition from normal to cancer cells, but the extent to which these alterations affect tumorigenesis in adenocarcinoma remains largely unknown. Herein we describe the application of mass spectrometry and multivariate statistical analysis in one of the largest biomarker r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
112
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(117 citation statements)
references
References 54 publications
5
112
0
Order By: Relevance
“…A few such studies showed promising results for gliomas (10, 11) and prostate cancers (12, 13). For lung cancer, previous metabolic profiling studies on cancer cell lines or tumors did not report new cancer-specific metabolites, presumably due to their focus on characterizing cancer-selective metabolic fluxes and pathways of common metabolites (14-22). …”
Section: Introductionmentioning
confidence: 99%
“…A few such studies showed promising results for gliomas (10, 11) and prostate cancers (12, 13). For lung cancer, previous metabolic profiling studies on cancer cell lines or tumors did not report new cancer-specific metabolites, presumably due to their focus on characterizing cancer-selective metabolic fluxes and pathways of common metabolites (14-22). …”
Section: Introductionmentioning
confidence: 99%
“…Metabolic markers have gained increased interest recently, as they are recognized as proximal markers to the disease phenotype in comparison to other ‘omics’ markers (4446). The footprint that products of altered tumor metabolism may leave in non-invasively collected biospecimens serves as a great opportunity for biomarker discovery.…”
Section: Discussionmentioning
confidence: 99%
“…Glycosylation changes have been observed in many cancers, including but not limited to liver[1316], pancreas[1720], lung [21, 22], breast [23], ovarian[24], colon[25] and prostate cancer[26, 27]. In many, proteins that contain these glycan changes have been identified.…”
Section: Discussionmentioning
confidence: 99%